The establishment of cyberpolitics: governance and code - Misseri, Lucas Emmanuel (2016)
This paper deals with the problem of politics in cyberspace. It deals with the hypothesis of a new and distinct institutional aspect that can be called “cyberpolitics”. This dimension is based on two founding forces: on one hand, the role of computer code in building the communicational network architecture (internet). On the other hand, the role of virtual communities as subjects that are constrained by this architecture but at the same time can modify it. These communities are organized by networked governance systems that make the cyber-political power horizontal, nevertheless they are no out of conflict.